Market liquidity and market making: The case of fixed income and low interest rates - Mark Strøm Kristoffersen; Jesper Pedersen (Danmarks Nationalbank, 2015)
Market liquidity and market making - the case of fixed income and low interest rates Market liquidity has received a lot of attention lately, especially in fixed-income markets. This paper studies the determinants of market liquidity in a theoretical model for market making with inventory costs, which is extended to the case of fixed-income securities. In the model, market makers provide liquidity to the market, which they are compensated for through the difference between the prices at which they buy and sell, the bid-ask spread. This spread is an often used measure for market liquidity. It is shown that under certain conditions, environments with low short-term interest rates can be characterised by lower market liquidity through wider bid-ask spreads compared to environments with higher interest rates. When interest rates are low, capital losses on the market makers' inventory holdings are more likely than when interest rates are higher, which leads to wider bid-ask spreads. – – Markedslikviditet og market making på obligationsmarkedet i et lavrentemiljø Markedslikviditet har været meget i fokus på det seneste, især på obligationsmarkedet. Niveauet af markedslikviditet analyseres i en lagermodel for market making, der udvides til at kunne beskrive obligationsmarkedet. I modellen stiller market makerne likviditet til rådighed for markedet, hvilket de kompenseres for via forskellen mellem deres købs- og salgspriser, bid ask-spændet. Dette spænd er et ofte anvendt mål for markedslikviditet. Det vises, at lavrentemiljøer under visse betingelser kan være kendetegnet ved større bid ask-spænd - og dermed lavere markedslikviditet - sammenlignet med perioder med et højere renteniveau. Kapitaltab på market makernes lagerbeholdning af obligationer er mere sandsynlige i et lavrentemiljø, end når renteniveauet er højere, hvilket giver et større bid ask-spænd.
Keywords: G12; G20; E43; 330; Market liquidity; market making; inventory costs; bid-ask spread; fixed income; low interest rates